Endogenous attention modulates attentional and motor interference from distractors: evidence from behavioral and electrophysiological results - Martín-Arévalo, Elisa; Lupiáñez, Juan; Botta, Fabiano; Chica, Ana B. (Frontiers in Psychology, 2015)
Selective visual attention enhances the processing of relevant stimuli and filters out irrelevant stimuli and/or distractors. However, irrelevant information is sometimes processed, as demonstrated by the Simon effect (Simon & Rudell, 1967). We examined whether fully irrelevant distractors (task and target-irrelevant) produce interference (measured as the Simon effect), and whether endogenous orienting modulated this interference. Despite being fully irrelevant, distractors were attentionally coded (as reflected by the distractor-related N2pc component), and interfered with the processing of the target response (as reflected by the target-related LRP component). Distractor’s attentional capture depended on endogenous attention, and their interference with target responses was modulated by both endogenous attention and distractor location repetition. These results demonstrate both endogenous attentional and motor modulations over the Simon effect produced by fully irrelevant distractors.